Hydrothermal Synthesis and Crystal Structure of A New 1D Chain Mn(II) Coordination Polymer - Shen, Bo; Li, Xianjiang (Asian Journal of Chemistry, 2013)
One new Mn(II) compound [Mn(L)(H2O)]·2H2On (H2L = 5-methylisophthalic acid) has been successfully synthesized. Compound shows a one-dimensional chain. The carboxylate group in compound adopt two coordination modes viz., bis-chelating and bis-monodentate modes.